Pengenalan tradisi Laras Madya dalam pembelajaran IPS melalui pendekatan konstruktivisme - Moch. Dimas Galuh Mahardika; Sariyatun Sariyatun (Universitas Negeri Malang, 2020)
Social science learning is an effort to provide student’s knowledge and comprehension about social condition in daily life. Basicly, social science is an integration of the study of social science such as, history, geography, economics, politic, sociology and other humanities science. So, the main purpose of social science learning to create the humans who are aware of their position as members of civil society. The introduction of local tradition also needs to be included in gerenal material on social science learning. Students are able to know more about existence of local tradition, one of wich is Laras Madya tradition. Laras Madya tradition is a one of the local tradition that can be inserted into the general social science learning materials. The approach to introduce this tradition is constructivism. Constructivism is an effective approach to use because can provides sufficient space for student to actively seek, collect, and process information to build their knowledge. This article is the author’s conceptual idea wich aims to provide a new reference about local tradition. DOI: http://dx.doi.org/10.17977/um022v5i22020p103